The Role of Lifestyle as a Mediator of The Influence of Financial Knowledge on Career Women’s Financial Behavior (JEM17: Jurnal Ekonomi Manajemen, 2023)
Women's financial knowledge is lower than men's paying attention because women control 80% of financial management. How well behaved in managing finances is determined by the level of financial knowledge. This study aims to understand how financial behavior is influenced by the level of financial knowledge and the role of lifestyle. The study focused on career women. Methods of quantitative approach and primary data were used in the study—data collection techniques by distributing questionnaires. A purposive sampling technique determined the total sample of 120 career women in Surabaya. Data analysis test with Structural Equation Modelling (SEM) technique using Smart PLS analyst tool Version 3.0. After the data analysis test was carried out, the results proved that financial knowledge affects financial behavior, lifestyle affects financial behavior and the existence of intermediaries from the lifestyle on the influence of financial knowledge on financial behavior. This research implies that the higher the financial knowledge career women have, the better their financial behavior, and they can improve their lifestyles to form appropriate and directed financial behaviors. Keywords: Financial Behavior, Financial Knowledge, Lifestyle.